2022
DOI: 10.1039/d2nj03058f
|View full text |Cite
|
Sign up to set email alerts
|

Axial ligand engineering for highly efficient oxygen reduction catalysts in transition metal–N4 doped graphene

Abstract: Developing highly efficient and stable electrocatalysts for oxygen reduction reaction (ORR) is a challenging task in energy conversion technologies. In this work, diverse axial ligands have been used to modify...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…To overcome experimental limitations, the effect of O axial ligands on model FeNC systems has been calculated by density functional theory (DFT), [14,15] although the effect of other possible axial ligands on different Fe sites (pyridinic and pyrrolic) has not been fully considered. [16] Alternatively, to improve catalyst performance, the number of active sites can be increased, an approach which has shown significant progress in recent years. [17] To selectively form a high density of atomic Fe sites and avoid undesired Fe-induced carbothermal reduction, Fellinger and co-workers first identified that the high temperature pyrolytic step (800-1000 °C) should be decoupled from the Fe loading, by using a suitable N x site template.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome experimental limitations, the effect of O axial ligands on model FeNC systems has been calculated by density functional theory (DFT), [14,15] although the effect of other possible axial ligands on different Fe sites (pyridinic and pyrrolic) has not been fully considered. [16] Alternatively, to improve catalyst performance, the number of active sites can be increased, an approach which has shown significant progress in recent years. [17] To selectively form a high density of atomic Fe sites and avoid undesired Fe-induced carbothermal reduction, Fellinger and co-workers first identified that the high temperature pyrolytic step (800-1000 °C) should be decoupled from the Fe loading, by using a suitable N x site template.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome experimental limitations, the effect of O axial ligands on model FeNC systems has been calculated by density functional theory, [14,15] although the effect of other possible axial ligands on different Fe sites (pyridinic and pyrrolic) has not been fully considered. [16] Alternatively, to improve catalyst performance, the number of active sites can be increased, an approach which has shown significant progress in recent years. [17] To selectively form a high density of atomic Fe sites and avoid undesired Fe-induced carbothermal reduction, Fellinger and coworkers first identified that the high temperature pyrolytic step (800-1000ºC) should be decoupled from the Fe loading, by using a suitable Nx site template.…”
mentioning
confidence: 99%
“…The CH 3 , benzene, benzene/NH 2 and benzene/ NO 2 ligands could improve the ORR activity of CrN 4 -Grad. 30 Zhou et al theoretically investigated the effects of axial ligands (L = -F, -Cl, -Br, -I, -OH, -O 2 , -CH 3 , -SCH 3 , -NH 2 , and -SCH 2 CH 3 ) on the ORR catalytic activity of FeN 4 , and confirmed that some axial ligands greatly enhanced the ORR catalytic activity of FeN 4 . 31 In recent years, Zhao et al reported that FePPc in which the Fe atom is axially coordinated with axial ligands (L = -F, -Cl, -Br, -I, -OH, -triethylamine (TEA), and -ethylenediamine (en)) (FePPc-L) was successfully prepared, and FePPc-I exhibited higher stability and ORR catalytic activity.…”
Section: Introductionmentioning
confidence: 96%